Design of Dual Band Microstrip Antenna for Wi-Fi and WiMax Applications - Raad H. Thaher; Zainab S. Jamil (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In this paper, a dual band rectangular microstrip patch antenna with microstrip line is presented. The proposed antenna is designed on FR4 substrate with thickness 1.5 mm and relative permittivity 4.3. The antenna is designed to operate at 2.4/5.8 GHz bands for Wi-Fi/WiMax applications. The obtained return loss is -32.77dB at 2.4 GHz with 7.4% bandwidth and -25.955 dB at 5.8 GHz with 8.17% bandwidth. The practical and simulation result are computed. It is noted that there is a good agreement between the simulation and measured result (using vector network analyzer (VNA)).